Statistični nadzor procesa: Praktikum (navodila za vaje pri predmetu Metode eksperimentalnega dela) - Črepinšek Lipuš, Lucija (University of Maribor Press, 2021)
Statistical Process Control: Practicum (Instructions for Exercises in the Subject Methods of Experimental Work). Practicum Statistical process control is a study tool for performing exercises in the subject Methods of Experimental Work. Short descriptions of basic quality management tools are followed by work tasks with procedures based on the principles of statistical verification of product quality. Exercises include performing measurements in the Laboratory for Technological Measurements and evaluating the results with the Excel software tool.